Maintenance model for series system with multiple vacation and CCF - Fang Li; Xianyun Meng (2011 International Conference on Multimedia Technology, 2011)
In order to achieve the long-run expected rewards and the average downtime of the system with repairman vacations and CCF, a series repairable system consisting of AT identical components is studied. By the theories of renewal process and geometric process, the expressions of the long-run expected rewards and the average downtime of the system are studied. Finally, a numerical example is given to illustrate some theoretical results in this paper. The simulation demonstrates that the optimal policy M = (N 1 , N 1 , N 3 ,...N k ) is existed. It is useful for improving the rewards of company and the safety critical system to make rational use of resources and equipments.